Job descriptions for bank personnel : a comprehensive guide - Bank Administration Institute (Park Ridge, Ill. : Bank Administration Institute, 1975)
This guide deals with numerous job descriptions, but because some banks do prepare and use job specifications, a distinctions is made between the two terms.
Includes index.
usc 17/07/2017
Loans
Keywords: Banks and banking; Banks and banking; United States